Pencarian Rute Tercepat Mobil Ambulance Menggunakan Algoritma Ant Colony Optimization - Angga Eka Prasetya (JURIKOM (Jurnal Riset Komputer), 2019)
One of the services provided by the hospital to patients is an ambulance team that is used as a transport to deliver patients or bodies to hospitals and funeral homes. In the service of ambulance teams requires speed and timeliness in minimizing patient risks. The fastest route is generally based on the shortest distance another point to point. In fact the best route should pay attention to road conditions such as road capacity, many vehicles passing through and so on. The method used for the research is the Ant Coloby Optimization algorithm, the method used is quite easy because it searches in depth with a better quality solution than using conventional conventional search methods so that it aims to design an ambulance route that can minimize the distance to patients and hospitals as a route who most likely have the fastest time.